2019
DOI: 10.1371/journal.pone.0217379
|View full text |Cite
|
Sign up to set email alerts
|

Simple methods to obtain food listing and portion size distribution estimates for use in semi-quantitative dietary assessment methods

Abstract: Semi-quantitative dietary assessment methods are frequently used in low income countries, and the use of photographic series for portion size estimation is gaining popularity. However, when adequate data on commonly consumed foods and portion sizes are not available to design these tools, alternative data sources are needed. This study aimed to develop and test methods to: (i) identify foods likely to be consumed in a study population in rural Uganda, and; (ii) to derive distributions of portion sizes for comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Cade et al [ 21 ] found that the agreement between FFQs and a reference dietary method was higher when portion size specified on the questionnaire (0.4–0.5) compared with no portion size specified (use of average portion weights to compute intakes: 0.2–0.5). Other scholars [ 43 ] hold the same opinion and emphasized common portion sizes for estimating nutrient intake more accurately. Open-ended questions rather than describing an accurate portion intend to decline the validity [ 44 ].…”
Section: Discussionmentioning
confidence: 94%
“…Cade et al [ 21 ] found that the agreement between FFQs and a reference dietary method was higher when portion size specified on the questionnaire (0.4–0.5) compared with no portion size specified (use of average portion weights to compute intakes: 0.2–0.5). Other scholars [ 43 ] hold the same opinion and emphasized common portion sizes for estimating nutrient intake more accurately. Open-ended questions rather than describing an accurate portion intend to decline the validity [ 44 ].…”
Section: Discussionmentioning
confidence: 94%